Analisis Kemampuan Numerasi Berdasarkan Kemampuan Awal Matematika pada Siswa Kelas V SD Negeri Sitibentar Tahun Ajaran 2023/2024 - Aulia Latifah; Muhammad Chamdani; Achmad Basari Eko Wahyudi (Universitas Sebelas Maret, 2024)
Based on the report cards of SD Negeri Sitibentar, numeracy skills are low and the scores are 1.57. It means that more than 50% of students fail in meeting the minimum competency. The study aimed to describe the numeracy ability based on early skills of fifth grade students at SD Negeri Sitibentar. It was descriptive qualitative. Data collection techniques were passive participant observation, tests (early mathematical skills and numeracy skills), in-depth interviews to students, and analysis of school profile documents. The results indicated that four students had good early skills meeting all indicators of numeracy ability, ten students gained moderate early skills meeting the second indicator but lacked in the first and third indicators, and five students met low early skills who did not master in all indicators. It concludes that the numeracy ability of fifth grade students at SD Negeri Sitibentar is low since 63.16% of students have difficulty in mastering indicators and calculating multiplication and division.